Certain Subclasses of Bistarlike and Biconvex Functions Based on Quasi-Subordination - Nanjundan Magesh; Vitalrao Kupparao Balaji; Jagadesan Yamini (Abstract and Applied Analysis)
We introduce the unified biunivalent function class Mq,σδ,λ(γ,φ) defined based on quasi-subordination and obtained the coefficient estimates for Taylor-Maclaurin coefficients |a2| and |a3|. Several related classes of functions are also considered and connections to earlier known and new results are established.